Explaining the link between gender and traffic accidents in Israel - Mazliach, Roni (Przegląd Prawniczy Uniwersytetu im. Adam Mickiewicza, 2015)
The aim of study is to explain the link between gender and traffic accidents in Israel. Traffic violations are considered as intentional deviations from practices that are crucial to maintaining safety while driving. These violations are commonly referred to as a significant factor in causing traffic accidents; therefore, when examining the case of traffic accidents it is extremely important to look at factors involved in traffic violations as well. This article serves only to propose the thesis of honour cultures as a significant local factor contributing to traffic accidents, but its resolution is much too wide to be able to base road-safety programs upon it. A further development of this idea, on a local basis, will thus be of great help in the field.